Comparison of Custodiol vs warm blood cardioplegia and conditioning of donor hearts during transportation with the organ care system. Issue 10 (23rd July 2019) - Kaliyev, Rymbay; Lesbekov, Timur; Bekbossynov, Serik; Bekbossynova, Makhabbat; Nurmykhametova, Zhuldyz; Novikova, Svetlana; Smagulov, Nurlan; Medressova, Assel; Faizov, Linar; Ashyrov, Zhanibek; la Fleur, Philip; Samalavicius, Robertas; et al.
Abstract: Objectives: Cold crystalloid cardioplegia for donor heart harvesting and cold ischemic storage conditions during the transportation is the standard of care during heart transplantation procedure. Organ care system (OCS) was introduced for more prolonged and reliable ex vivo organ management. This study evaluated the two different techniques used for myocardial preservation during the procurement and transportation of the heart using the OCS. Methods: We performed prospective analysis of 43 patients with heart failure undergoing heart transplantation and using the OCS for donor organ transport. Donor hearts were arrested using blood cardioplegia and conditioning ( n  = 30) or standard Custodiol (SC) solution ( n  = 13). Perfusion and cardiac function parameters were continuously monitored while the donor hearts were perfused in the OCS. Impact of preservation techniques on biochemical parameters and clinical outcomes were evaluated. Results: All donor hearts had stable perfusion and lactate characteristics in the OCS, with similar measures between the two groups at the beginning of the ex vivo perfusion. Ex vivo heart perfusion mean ending concentration of Interleukin (IL)‐6 and IL‐8 was significantly lower in the blood cardioplegia group compared to the standard care group. Clinical outcomes were comparable between the two groups of patients. Conclusions: The use of blood cardioplegia and conditioning could be a safe method for myocardial protection in distant procurement and preservation of donor hearts in the OCS.